Kant’s Aesthetic Reading of Aristotle’s "Philia": Disinterestedness and the Mood of the Late Enlightenment - Jaques Pi, Jèssica (Revista de Filosofía, 2012)
This article roots Kant’s concept of disinterestedness, as he uses it in the Critique of Judgment, in Aristotle’s notion of philia by establishing a path from ethics to aesthetics and back. In this way, the third Critique turns out to be one of the main sources for a new ideal of humanity: the ideal suitable for late Enlightenment. This article argues that Kant reaches this fruitful use of disinterestedness by giving to Aristotle’s concept of philia an aesthetic turn.